Development of Polish-Portuguese bilingualism in Brazil - Kukawska , Agata Edyta (Biuletyn Historii Wychowania, 2023)
The aim of the article is to show the Polish-Brazilian evolution of bilingualism throughout ages. his paper shows different definitions and types of bilingualism, taking into consideration a comparison between the Polish and Portuguese language. Furthermore, I present a review of 150 years of Polish citizens’ history in Brazil. It presents their difficulties and the approach of the Brazilian government from the 19th to the 20th century. The most significant subject are Polish schools and organizations. Their history shows how the command of Polish and Portuguese changed throughout ages. There were different conditions, affecting the command of languages in the Polish Diaspora, such as the familial approach or access to Polish culture. I also mention which organizations and people had the biggest impact on Polish citizens in Brazil. I also describe the existing attitude to both cultures and languages in Polish communities. Apart from that, I try to understand the identity and acquaintance of Polish culture nowadays and show actions as a resultof which Polish language and history are promoted nowadays.